Adenosine triphosphate/adenosine guided pulmonary vein isolation does not improve the outcomes of ablation: a meta-analysis of randomized controlled trials. (4th May 2018) - Afzal, Muhammad R.; Kahaly, Omar; Weiss, Raul; Houmsse, Mahmoud; Daoud, Emile G.; Hummel, John D.
ABSTRACT: Background : Successful pulmonary vein isolation (PVI) is the most reliable predictor of success after ablation in patients with atrial fibrillation (AF). Adenosine triphosphate (ATP) unmasks the dormant conduction and can be used to improve the effectiveness of PVI. The impact of ATP guided PVI on clinical outcomes is discordant in various randomized controlled trials (RCTs). Objectives : To delineate the incremental benefit of ATP during PVI in patients with AF through a meta-analysis. Methods and results : Database searches through January 2017 identified 5 RCTs (enrolling 2839 patients) comparing ATP guided PVI versus standard PVI (non-ATP). Four trials exclusively studied paroxysmal AF while one trial included both paroxysmal and non-paroxysmal AF patients. Baseline characteristics, dose of adenosine and ablation strategies were clearly identified among all the trials. The risk ratio (RR) for AF episodes lasting >30 s after 3-month blanking period was calculated with random effects meta-analysis and showed no difference at a median follow up of 12 months [RR: 1.02, 95 % Confidence interval (CI): 0.85 to 1.25; p = 0.82]. Similarly, the number of repeat ablation was similar in both groups [RR: 1.02, 95 % CI: 0.63, 1.56; p = 0.98]. Conclusions : ATP guided PVI does not decrease the recurrence of AF or the need for repeat ablation at 12 months.